PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DESA (PROGRAM ALOKASI DANA DESA DI DESA BUNTONGI KECAMATAN AMPANA KOTA) - Hardianti, Sri (Katalogis, 2017)
This study aims to determine and analyze the level of community participation as well as aspects related to the level of community participation in the implementation of rural infrastructure development. The approach used in this study is a qualitative approach with purposive sampling techniques and the data were collected through interviews and delivered questionnaires. Then, the data were analysed by qualitative approach and it was supported by quantitative data. The results of this study show that: First, the level of community participation in the implementation of the program of Village allocation fund) in Buntongi village is still low. Second, the aspects related to public participation in the implementation phase namely the type of employment and income. Meanwhile the level of education only affects the planning stage as well as monitoring and evaluation.